Inhibition of malignant potential and expression of proteins associated with epithelial-mesenchymal transition in Lewis lung carcinoma cells transduced with murine ifn-β gene in recombinant baculovirus - Lykhova, O.; Kovalova, O.; Bezdenezhnykh, N.; Adamenko, I.; Vorontsova, A.; Strokovska, L.; Kudryavets, Yu. (Experimental Oncology, 2016)
Aim: To analyze biological characteristics. malignant potential and expression of proteins associated with epithelial mesenchynal
transition in murine lung carclnoma cells transduced with intertcron-beta (ifn-β) gene in baculovirus vector. Materials and Methods: The study was perforated on Lewis lung carcinoma (LL) cells transduced with ifn-β gene in recombinant baculovirus vector.
Biological characterlstics of the LL cells were studied with the use of standard cell culture method, cytogenetic and immunocytochemical assays. Resutes: Recombinant baculmirus-mediated transduction of LL cells with ifn-β gene resulted in siguﬁcant decrease
of cell growth rate and density both in complete and serum-foee medium. Also. LL cells transduction with ifn-β gene signiﬁcantly
inhﬂtited cell migration in vitro. Transduction of LL cells by baculovirus vector with or withoot ifn-β gene caused signiﬁcant genotoxic effect in these cells. Furthermore. ifn-β gene transfer to lung carcinoma cells resulted in signiﬁcant increase of nuclear expression of p19ARE (p < 0.01). p21WAFI (p < 0.001). cytoplasmic expression of E-cadherin (p < 0.005) and inhibition of transcription
factors of epithelial-mesenchymal transition (EMT) Tmist (p < 0.005) and Slug (p < 0.00 I) expression. Conclusions; Transduction
with ifn-β gene of LL cells in recombinant baculovirus resulted in aquirement of less malignant phenotype in vitro and suppressed
expression ofproteins associated with EMT.